High-throughput calculation-based rational design of Fe-doped MoS2 nanosheets for electrocatalytic pH-universal overall water splitting - Hai, Guangtong; Xue, Xiangdong; Wu, Zhenyu; Zhang, Canyang; Liu, Xin; Huang, Xiubing (Journal of energy chemistry, 2024)
The high-performance single atom Fe-doped MoS2 electrocatalyst was identified and prepared by means of high-throughput computing-aided rational design for overall water splitting. [Display omitted] Electrocatalytic water splitting is crucial for H2 generation via hydrogen evolution reaction (HER) but subject to the sluggish dynamics of oxygen evolution reaction (OER). In this work, single Fe atom-doped MoS2 nanosheets (SFe-DMNs) were prepared based on the high-throughput density functional theory (DFT) calculation screening. Due to the synergistic effect between Fe atom and MoS2 and optimized intermediate binding energy, the SFe-DMNs could deliver outstanding activity for both HER and OER. When assembled into a two-electrode electrolytic cell, the SFe-DMNs could achieve the current density of 50 mA cm−2 at a low cell voltage of 1.55 V under neutral condition. These results not only confirmed the effectiveness of high-throughput screening, but also revealed the excellent activity and thus the potential applications in fuel cells of SFe-DMNs.